OS-FMEA and AI in occupational health: new strategies for risk assessment and mitigation in vaccination room - Cavaignac, André Luís de Oliveira; Alves, Amanda Cristina da Silva; Ferreira, Viviane Sousa (Brazilian Journal of Production Engineering, 2025)
Occupational accidents involving sharp objects and exposure to biological agents are frequent among healthcare professionals in Brazil, and the constant reporting of these events reflects an insufficient application of biosafety standards. This work is based on feeding an AI with a theoretical/technical framework and, after prior training, having it evaluate an image/photograph of a function/task of a sector or worker, returning with a complete analysis by generating an ETA (Ergonomic Task Analysis) and an OS-FMEA (Occupational Safety FMEA). To apply this methodology, the function of a vaccine agent in a UBS was taken. As preliminary results, the AI was able to analyze the image, score the related occupational risks, and propose corrective actions, generating an ETA. In addition, the AI was able to generate an analysis of the function through the OS-FMEA and, after applying the corrective actions suggested by it in a hypothetical situation, obtain a reduction in RPNs (risk priority numbers). In this work, a table of Occurrence x Severity x Detection (OxSxD) concepts specific to healthcare workers was also obtained. updated with publicly available data up to 2022.